Filosowiecki tryb cenzury filmowej we Włoszech epoki zimnej wojny – kontekst i studia przypadków - Jóźwiak, Karol (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Despite Italy participating in the western alliance during the Cold War, anticommunism is quite absent from Italian movies. Any explicit criticism of the Soviet regime is a rarity in Italian cinema of the early Cold War period as well. The Soviet regime is never denounced as a totalitarian state, and seldom approached in a critical manner. Rare examples of films containing criticism of the Soviet Union usually faced difficulties at the level of development, censorship, and distribution. Surprisingly, this issue is not tackled by Italian film studies, and particularly by those focusing on censorship. This article addresses the issue of philosovietic mode of film censorship, the reason why it is misrepresented in film criticism and film history, and also the relevance of this issue in the current geopolitical situation.